Ảnh hưởng của các chất tạo cấu trúc tới sự hình thành xúc tác VAPO - Huyền và cộng sự, Phạm Thanh (Vietnam Journal of Chemistry, 2014)
Vanadium aluminophosphates (VAPO) are good catalysts for oxidation reaction and they are being interested by many scientists. In this paper, the synthesis of VAPOs from aluminum sulfate, phosphoric acid, vanadium pentoxide with different templates is reported. The role of these templates is explained. The catalysts were characterized by XRD, IR and SEM.